Multimodal Brain Image Analysis First International Workshop, MBIA 2011, Held in Conjunction with MICCAI 2011, Toronto, Canada, September 18, 2011. Proceedings - Liu, Tianming; Shen, Dinggang; Ibanez, Luis.; Tao, Xiaodong; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the First International Workshop on Multimodal Brain Image Analysis, held in conjunction with MICCAI 2011, in Toronto, Canada, in September 2011. The 15 revised full papers presented together with 4 poster papers were carefully reviewed and selected from 24 submissions. The objective of this workshop is to facilitate advancements in the multimodal brain image analysis field, in terms of analysis methodologies, algorithms, software systems, validation approaches, benchmark datasets, neuroscience, and clinical applications.
Keywords: Electronic books; Computer science; Radiology, Medical; Computer software; Artificial intelligence; Computer graphics; Computer vision; Optical pattern recognition; Pattern Recognition; Image Processing and Computer Vision; Artificial Intelligence (incl. Robotics).; aAlgorithm Analysis and Problem Complexity; Imaging / Radiology